KERALA ECONOMY: GROWTH, STRUCTURE, STRENGTH AND WEAKNESS - K.K. GEORGE (Centre for Socio-economic & Environmental Studies(CSES), 2011)
This paper follows the course of Kerala economy from the early historic period till date. It argues that contrary to popular impressions and scholars’ narratives, the state’s economy was growing when the foundations of Kerala’s human development were laid. This period of expansion was followed by a prolonged period of slackening economic growth (1955-56 to 1986-87). There was a turnaround in economic growth from 1987-88. The economy despite the high growth suffers from some major weaknesses. But the paper argues that Kerala has sufficient potential for much faster economic development in the context of globalized world and knowledge society, provided there is a change in the mindset of the people, government, political parties, civil society and the media